Original paper Improved source path localisation in ring applicators and the clinical impact for gynecological brachytherapy - Humer, Irene; Kirisits, Christian; Berger, Daniel; Trnková, Petra; Pötter, Richard; Nesvacil, Nicole (Journal of Contemporary Brachytherapy, 2015)
Purpose: The path of subsequent dwell positions of an afterloader source being moved through a ring applicator for cervix cancer brachytherapy deviates from an ideal circle and the position of marker wires. This can lead to deviations of several millimetres between real and assumed dwell positions for treatment planning with simplified source path models. The aim of this study was to test video- and autoradiography-based methods for source path determination, and to study the influence of dwell position accuracy on dose-volume histogram (DVH)-parameters. Material and methods: Videos of the exact motion of the source wire through three different (r = 26, 30, 34 mm) computed tomography/magnetic resonance (CT/MR) compatible plastic ring applicators were recorded. Observed dwell positions covering the whole length of each applicators channel were used to adjust the circular source path model. The agreement of the true source positions derived from video analysis with those of the corrected circular source path was verified using autoradiography. The impact of an accurate source path definition on dose planning was analysed by simulating clinically relevant uncertainties in 10 clinical treatment plans. Results: Depending on the ring size, source path diameters had to be increased by 0.5-1.0 mm in order to achieve acceptable maximum differences between observed and corrected dwell positions (1.3-2.0 mm). Autoradiography analysis showed a positional accuracy within ± 3 mm (extended standard deviation k = 2). For shifts of ± 2.5 mm for even all dwell positions, the systematic and random variation of the D2cmł for bladder, rectum, and sigmoid was within 3%, while the impact on DVH uncertainties was much smaller for clinical target volume (CTV)HR and gross tumour volume (GTV). Conclusions: It is strongly advised to verify the real source path for ring applicators during acceptance testing in order to assure accurate source path definition and dose planning. Autoradiography can be used for source path verification with acceptable accuracy for treatment planning and dose reporting.